Ingestion of Fluids of the Ocular Surface Containing Eye Drops of Imidazole Derivatives-Alpha Adrenergic Receptor Agonists as Paragons - Ivan Šoša (MDPI AG, 2024)
Accidental poisonings by ingesting conjunctival fluid mixed with eye drops commonly involve alpha-2 adrenergic receptor agonists and tetrahydrozoline. These substances are recognized in commonly reported ingestions. Victims of all ages, otherwise in good health, often present as pale and lethargic to the emergency department (ED) after unintentionally ingesting topical eye medication. While eye drop poisoning cases in childhood include accidents during the play and poisonings in adults mean either suicide attempts or side effects caused by the systemic absorption of the substance, fluid of the ocular surface is a risk to all age groups. With this in mind, this study aimed to summarize data in the literature on tetrahydrozoline and alpha-2 adrenergic receptor agonists as dangerous medications, even when administered in low-bioavailability forms, such as eye drops. With this aim, a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-compliant systematic review of relevant studies was conducted. A search of PubMed, Scopus, Web of Science, and EBSCOhost yielded nine studies that met the rigorous inclusion criteria. The primary studies were subject to a meta-analysis once a quality appraisal of the studies and a narrative synthesis of the extracted data had been conducted. The author hopes that this information will provide observations that will lead to better designs for over-the-counter eye drops, off-label drug usage policies, and parental attention.